2017
DOI: 10.5301/maapoc.0000017
|View full text |Cite
|
Sign up to set email alerts
|

Medicines Counterfeiting in Africa: A View from Zimbabwe

Abstract: With the sprouting of unregulated outlets on the streets of Zimbabwe, common questions that are raised include: (i) what is the Medicines Control Authority of Zimbabwe (MCAZ) doing about these street vendors? and (ii) is the law against unregulated markets and proliferation of substandard and falsified (SF) medicines being actively enforced? There is no doubt that this is a new challenge for MCAZ because of the risks involved with SF medicines. Notwithstanding the rather strong regulatory framework for the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Strategies to curb the spread of SARS-CoV-2, such as international travel and trade restrictions at the onset of the COVID-19 pandemic, led to supply chain disruptions and pharmaceutical regulatory governance challenges that created opportunities for the increased influx of falsified, substandard drugs [ 23 , 26 , 27 , 28 ]. While the precise market share of informal street markets in low- and middle-income countries is unknown, a study in Nigeria suggested that more than 40% of rural communities consult and purchase drugs from street vendors for illnesses such as childhood fevers [ 25 , 29 , 30 ]. The use of counterfeit vaccines and antimicrobials leads to the development of new SARS-CoV-2 variants and the emergence of AMR.…”
Section: Drivers Of Antimicrobial Resistance In the Covid-19 Eramentioning
confidence: 99%
“…Strategies to curb the spread of SARS-CoV-2, such as international travel and trade restrictions at the onset of the COVID-19 pandemic, led to supply chain disruptions and pharmaceutical regulatory governance challenges that created opportunities for the increased influx of falsified, substandard drugs [ 23 , 26 , 27 , 28 ]. While the precise market share of informal street markets in low- and middle-income countries is unknown, a study in Nigeria suggested that more than 40% of rural communities consult and purchase drugs from street vendors for illnesses such as childhood fevers [ 25 , 29 , 30 ]. The use of counterfeit vaccines and antimicrobials leads to the development of new SARS-CoV-2 variants and the emergence of AMR.…”
Section: Drivers Of Antimicrobial Resistance In the Covid-19 Eramentioning
confidence: 99%
“…Such exposure presents a major health challenge as the market is likely to be proliferated with SF [substandard & falsified] pharmaceutical products for major diseases such as antiretroviral therapy (ART) anti-tuberculosis (anti-TB), anti-malarial therapy and other essential medicines. (Gwatidzo et al, 2017 , p. 82)…”
Section: Findings: How the Published Literature Negotiate And Manage mentioning
confidence: 98%
“…For example, one paper paints a picture of how fakes – both medicines and non-medical products – were presented to inquisitive passers-by and presumably potential consumers: Such exposure presents a major health challenge as the market is likely to be proliferated with SF [substandard & falsified] pharmaceutical products for major diseases such as antiretroviral therapy (ART) anti-tuberculosis (anti-TB), anti-malarial therapy and other essential medicines. (Gwatidzo et al, 2017 , p. 82) Here, the possibilities of the market extend claims about fakes’ threat to health by using the extent of their reach (Hornberger, 2018 ) as indicative of ‘evidence gaps’. Similar claims were made about the absence of regulation in online markets (Interpol, 2014 ; see also discussion by Clark, 2015 ).…”
Section: Findings: How the Published Literature Negotiate And Manage mentioning
confidence: 99%
“…For example, when medicines are not affordable through the formal regulated health system due to prohibitive costs or lack of national health insurance schemes, patients will be driven to seek these through other routes, where regulatory oversight may be compromised and there is a greater risk that the medicine will be substandard or falsified. 14 This has been highlighted in Morocco where unaffordable medicines were implicated in driving medicine’s trafficking from Algeria and sold at markets, where the quality and validity were unknown. 15 …”
Section: Framing Quality Medicines Supply Within a Health System Contextmentioning
confidence: 99%